Epictia collaris (Hoogmoed, 1977) (Reptilia: Squamata: Leptotyphlopidae), new record for the herpetofauna of Amapá and Brazil, with additional localities in French Guiana and a distribution map - Hoogmoed, Marinus S.; Lima, Jucivaldo Dias (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2018)
Epictia collaris is reported for the first time from Amapá and Brazil. We provide a map with all known localities of this species in Suriname, French Guiana, and Brazil. Some new data on habitat and colour in life are presented.